2012
DOI: 10.1155/2012/375217
|View full text |Cite
|
Sign up to set email alerts
|

Loss to Followup in HIV-Infected Patients from Asia-Pacific Region: Results from TAHOD

Abstract: This study examined characteristics of HIV-infected patients in the TREAT Asia HIV Observational Database who were lost to follow-up (LTFU) from treatment and care. Time from last clinic visit to 31 March 2009 was analysed to determine the interval that best classified LTFU. Patients defined as LTFU were then categorised into permanently LTFU (never returned) and temporary LTFU (re-entered later), and these groups compared. A total of 3626 patients were included (71% male). No clinic visits for 180 days was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 33 publications
7
40
4
3
Order By: Relevance
“…Estos 210.000 individuos con carga viral indetec- El programa de HIV/sida del Hospital Universitario San Ignacio presentó una tasa de densidad de la incidencia de la pérdida en el seguimiento de 17,74 por 100 personas por año, mucho más alta que la observada en otros estudios (3,72; 5,1 y 9,1 por 100 personas por año) (18)(19)(20), aunque en otras poblaciones se han descrito tasas de pérdida en el seguimiento superiores a lo reportado en este estudio (25,1 y 21,4 por 100 personas por año) (21,22). Las diferencias entre los estudios podrían deberse a las diversas metodologías aplicadas, así como a diferencias en la definición de pérdida en el seguimiento, en los tiempos de seguimiento de los estudios, en las poblaciones infectadas con HIV estudiadas y en las estructuras médicas locales (18,20).…”
Section: Discussionunclassified
“…Estos 210.000 individuos con carga viral indetec- El programa de HIV/sida del Hospital Universitario San Ignacio presentó una tasa de densidad de la incidencia de la pérdida en el seguimiento de 17,74 por 100 personas por año, mucho más alta que la observada en otros estudios (3,72; 5,1 y 9,1 por 100 personas por año) (18)(19)(20), aunque en otras poblaciones se han descrito tasas de pérdida en el seguimiento superiores a lo reportado en este estudio (25,1 y 21,4 por 100 personas por año) (21,22). Las diferencias entre los estudios podrían deberse a las diversas metodologías aplicadas, así como a diferencias en la definición de pérdida en el seguimiento, en los tiempos de seguimiento de los estudios, en las poblaciones infectadas con HIV estudiadas y en las estructuras médicas locales (18,20).…”
Section: Discussionunclassified
“…The LTFU rate is of concern as since 2006 LTFU has equated to 6.6% of potential follow-up on ART. A recent analysis of TAHOD data demonstrated that patients with shorter HIV infection history, poorer response to antiretroviral treatment, and infrequent or no clinical monitoring were at higher risk of LTFU, 32 and thus are a group that warrant additional support to prevent LTFU.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for LTFU were not calculated as they had been already been determined recently using TAHOD data. 32 For comparison between < 2006 and from 2006, we used a rank_sum test for continuous variables, t-test for proportions, and Mantel-Cox rate ratio for TI and LTFU rates.…”
Section: 31mentioning
confidence: 99%
“…No additional post-LTFU patient tracing was conducted as part of this study. The 180 day cut-off was selected as this has previously been validated in our cohort to achieve the highest sensitivity and specificity for determining LTFU patients 27,28 . Re-engagement into care after the first LTFU event was not considered.…”
Section: Methodsmentioning
confidence: 99%